A Sulfated Galactan with Antioxidant Capacity from the Green Variant of Tetrasporic Gigartina Skottsbergii (Gigartinales, Rhodophyta) - Encina-Rojas, M; Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B (2012)
The water soluble polysaccharide produced by the green variant of tetrasporic Gigartina skottsbergii was found to be composed of d-galactose and sulfate groups in a molar ratio of 1.0:0.65. 1H and 13C NMR spectroscopy studies of the desulfated polysaccharide showed a major backbone structure of alternating 3-linked ?-d-galactopyranosyl and 4-linked ?-d-galactopyranosyl units, and minor signals ascribed to 3-O-methyl-substitution on the latter unit. Ethylation analysis of the polysaccharide indicated that the sulfate groups are mainly located at position O-2 of 4-linked ?-d-galactopyranosyl residue and partially located at positions O-6 of the same unit and at position O-2 of 3-linked ?-d-galactopyranosyl residue, and confirmed the presence of 3-O-methyl-galactose in minor amounts (4.4%). The sulfated d-galactan presents a similar structure to ? carrageenan but with much lower sulfation at position O-6 of the ?-residue and at position O-2 of ?-residue. The antioxidant capacity of the sulfated d-galactan was evaluated by the peroxyl radicals (ORAC method), hydroxyl radicals, chelating activity, and ABTS + assays. Kinetic results obtained in these assays were compared with those obtained for the commercial ? carrageenan. The antioxidant activity toward peroxyl radicals was higher for commercial ? carrageenan, this agrees with its higher content of sulfate group. The kinetics of the reaction of both polysaccharides with hydroxyl and ABTS + radicals showed a complex mechanism, but the antioxidant activity was higher for the polysaccharide from the green variant of tetrasporic Gigartina skottsbergii. © 2011 Elsevier Ltd. All rights reserved. 51.